Seasonal Variation in Phytoplankton Community Structure at Sichang Island and Chonburi Coastal Area - Gunbua, Vichaya; Kingkaew , Napittha (Burapha Science Journal, 2026)
The community structure and seasonal variation of phytoplankton at Sichang Island and Chonburi coastal area were studied. The water samples were collected in March 2020 (Summer season) and August 2020 (Rainy season) from 16 stations. The results found the phytoplankton in 51 genus, 4 classes and 2 divisions (Cyanophyta and Chromophyta). The Cyanophyta (Cyanobacteria) class Cyanophyceae found 3 genus and the dominant specie was Trichodesmium. The Chromophyta class Bacillariophyceae (diatom) found 35 genus and the dominant species were Thalassiosira, Thalassionema and Chaetoceros and class Dinophyceae (dinoflagellate) found 12 genus and the dominant species were Tripos and Dinophysis and class Dictyochophyceae (silicoflagellate) found 1 genus was Dictyocha. The results showed the abundance of phytoplankton in August was equal to 86,321 cells per liter while in March as 5,599 cells per liter. The similarity index showed the phytoplankton was divided into 2 groups (August and March). The cause of difference may be from the salinity factor which led to the changes of phytoplankton community structure.